Hepatobiliary disorders associated with TNF-α inhibitors: a pharmacovigilance analysis of FAERS and JADER - Chen, Hongyu; Jiang, Shirui; Wang, Jingyu; Zhang, Ailin; Zhu, Liqin (Frontiers in Immunology, 2026)
IntroductionTumor necrosis factor-a (TNF-a) inhibitors are widely used for immune-mediated diseases. Their systemic adverse events (AEs) have become increasingly prominent. The hepatobiliary risks of different TNF-a inhibitors were compared in this paper to serve for their screening in clinics. MethodsWe analyzed the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) data and Japanese Adverse Drug Event Report Database (JADER) data for five TNF-a inhibitors (adalimumab, etanercept, infliximab, certolizumab pegol, golimumab) listed as primary suspects. Disproportionality analyses identified hepatobiliary safety signals. Logistic regression assessed risk factors. ResultsAcross FAERS and JADER, adalimumab showed a positive hepatobiliary signal [ROR: 1.42 (1.39, 1.45) in FAERS and 1.39 (1.20, 1.62) in JADER].For adalimumab, risk was higher in men [OR: 1.225 (1.082, 1.386) in FAERS and 2.378 (1.517, 3.726) in JADER] and with higher dose [OR: 1.073 (1.049, 1.098) in FAERS], higher age [OR: 1.168 (1.032, 1.321) in JADER], greater weight [OR: 1.363 (1.192, 1.557) in JADER], and several co-reported categories which included skin and subcutaneous tissue disorders [OR: 1.247 (1.084, 1.434) in FAERS and 2.432 (1.100, 5.437) in JADER]. ConclusionThe robust signal between adalimumab and hepatobiliary adverse events was observed in our study. Male sex and skin and subcutaneous tissue disorders were regarded as consistent independent risk factors. The factors of drug dose, body weight, and additional comorbidity clusters could also require attention in clinics because these factors were obviously observed in certain single databases.